If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -4 = -4p + -11 + 5p Reorder the terms: -4 = -11 + -4p + 5p Combine like terms: -4p + 5p = 1p -4 = -11 + 1p Solving -4 = -11 + 1p Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '-1p' to each side of the equation. -4 + -1p = -11 + 1p + -1p Combine like terms: 1p + -1p = 0 -4 + -1p = -11 + 0 -4 + -1p = -11 Add '4' to each side of the equation. -4 + 4 + -1p = -11 + 4 Combine like terms: -4 + 4 = 0 0 + -1p = -11 + 4 -1p = -11 + 4 Combine like terms: -11 + 4 = -7 -1p = -7 Divide each side by '-1'. p = 7 Simplifying p = 7
| M/-16=-9 | | y-9=15(x-5) | | 13=3p-15-2p | | x^2+24x-23=0 | | 8x^2-28x+98=0 | | 8x^2-28+98=0 | | 38x-14=20 | | 2(x-2)=-3x+21 | | 2+3.8= | | 3(2a-4)= | | 2(x-2)=-3+21 | | 3a+50=140 | | -9-6=8+x | | (y^2-7)(5y^2-5y+6)= | | 2+38= | | -13=7p-12-6p | | 36r^9-9r^6+54r^3= | | 7(3x-4)=17x | | x+6/5+x-1/4=2 | | 11=8p-14-7p | | n^2=4n+5 | | 1/2y-1/3x-1=0 | | -3=3p+11-2p | | 6=-6p-10+7p | | a+3ab-4ab= | | 3x-5+9x=-15 | | 8x^3-49x^2+6x=0 | | -8+10=9x+17 | | 1+a+x^2=p | | -9=-6p-7+7p | | y-4=(x-7)(x-7) | | 3=-4.5+4y |